Histopathology of the Gill of Pangasianodon hypophthalmus that were Fed with Fermented Red Ginger to Prevent Motile Aeromonas Septiceamia Disease - Muhammad Arga Saputra; Morina Riauwaty; Henni Syawal (Jurnal Natur Indonesia, 2022)
Red ginger is a natural ingredient that contains several antibacterial compounds such as essential oils, flavonoids, terpenoids, phenols, and zingiberene. This research was conducted from June to August 2021. The purpose of this study was to analyze the structure of the gill and liver tissue of jambal siam fish and to obtain the best dose of adding fermented red ginger to the feed before and after being challenged with Aeromonas hydrophila bacteria. The method used is an experimental method using a one-factor Completely Randomized Design (CRD) with five treatment levels and three replications, namely: Feeding without fermentation of red ginger and without being tested against A. hydrophila (Kn), Feeding without fermentation of red ginger and tested against A. hydrophila (Kp), Feeding with a dose of 150 mL/kg (P1), dose 175 mL/kg feed (P2), dose 200 mL/kg (P3). The results showed that the structure of the gill tissue of Jambal Siam fish showed damage such as hypertrophy, hyperplasia and bent lamellae. The best results were found in the P2 treatment, a  dose of 175 mL/kg feed and tested against A.hydrophilla bacteria